Лінгвософія сучасного гумору й сатири в журналі "Перець" - Коць, Т. (Культура слова, 2019)
Стаття присвячена аналізові мовних засобів гумору й сатири в журналі «Перець». Особливу увагу звернено на ядерні поняття текстів (влада, соціальна сфера, економіка), навколо яких формуються сатирично-гумористичні парадигми оцінних мовних засобів. Гумористично-сатиричний ефект досягається поєднанням високого й низького стилів, об’єднанням в одному ряду неоднорідних предметів, контекстуальною логічною невідповідністю, повтором багатозначних слів, нагромадженням синонімів, уживанням перифраз трансформованих народнорозмовних фразеологізмів. Основна функція сміху на сучасному етапі життя суспільства полягає в зведенні до мінімуму соціального стресу, в адаптації суспільства до докорінної зміни соціокультурних цінностей, у максимально безболісному сприйманні щоденних побутових труднощів. The article is devoted to the analysis of linguistic means of humor and satire in Magazine «Perets». Particular attention is paid to the nuclear concepts of texts (power, social sphere, economy) around which the satirical-humorous paradigms of language are formed. Humorous-satirical effect is achieved by combining high and low styles, combining in one row of heterogeneous objects, contextual logical inconsistency, repetition of ambiguous words, accumulation of synonyms, use of the periphery of transformed folk-speaking phraseologies. The main function of laughter at the present stage of society is to minimize social stress, to adapt the society to a radical change in socio-cultural values, to maximize painless perception of daily household difficulties. The content of Magazine «Perets» remains an expression of nationalintellectual humor, a testament to the moral and psychological health of Ukrainians, who, laughing, saying goodbye to the past, trying to change contemporary realities, establish themselves, and preserve universal values.It became the main illustrated satirical-humorous magazine, a manifestation of the defensive reaction of Ukrainians against various threats, authorities, authorities, the fixator of Ukrainian noble laugh culture.Since the end of the twentieth century. the edition is dominated by satirical texts with a sharply revealing character with elements of sarcasm, the defining feature of which is malleability, documentalism, exposition of important social phenomena, important social events.